1934
DOI: 10.1098/rstb.1934.0019
|View full text |Cite
|
Sign up to set email alerts
|

V - Some features of the action of the utricular maculæ (and of the associated action of the semicircular canals) of the frog

Abstract: As is well known, the operation of unilateral labyrinthectomy produces a persistent leaning of the head accompanied by spinal torque. Breuer (1875) once ventured to suggest that damage to the utriculus might be responsible for this effect. Subsequent work by many observers, e.g ., Laudenbach (1899), G. H. Parker (1908, 1909), Benjamins (1920), Maxwell (1920), Manning (1924), McNally and Tait (1925), Versteegh (1927), von Frisch and Stetter (1932), has tended to support this original con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1940
1940
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…It has been shown that in the frog the utricles serve to stabilize the head [Tait and McNally, 1934]. It is difficult to see how this could be achieved unless these end organs made information rapidly available to the C.N.S.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in the frog the utricles serve to stabilize the head [Tait and McNally, 1934]. It is difficult to see how this could be achieved unless these end organs made information rapidly available to the C.N.S.…”
Section: Discussionmentioning
confidence: 99%
“…As this tonus asymmetry is accentuated by 410 FUNCTION OF OTOLITH ORGANS a tilt to the normal position, and is least noticeable when the animal comes to rest lying on its operated side, the conclusion was naturally reached that the otolith organ responsible for the perception of lateral tilts is maximally stimulated when the labyrinth is lowered. The findings of Tait & McNally (1934) in what they call the uni-soliutricular frogs, in which all labyrinthine receptors except one utriculus were eliminated by nerve cutting, also point towards ipsilateral preponderance of the anti-gravity muscles under the influence of the intact vestibular end organ. In agreement with this, allrecords obtained from the vestibular nucleus of the mammalian brain stem (Adrian, 1943) show increased impulse discharge on side-down tilting, which has been tentatively attributed to the activity of the ipsilateral sacculus.…”
mentioning
confidence: 92%
“…Although it is very tempting to adopt some such ad hoc scheme of explanation, it must be said that the pattern of functional integration is probably more complicated. A significant indication that this may be so, is the fact that Tait & McNally (1934), in their interpretation of elimination experiments on the frog's labyrinth, found themselves forced to abandon the prevailing idea that the otolith 'acts by a simple and uniform sliding descent from a higher to a lower level' and came to the conclusion that a 'hypothesis of a point-to-point independence of the elements composing the otolith organs is unavoidable'.…”
mentioning
confidence: 99%
“…In frogs with only one utricle intact, Tait and McNally (65) found diametrically opposed compensatory and anticompensatory reactions resulting from a slow or a quick tilt in the same direction around a horizontal axis. These authors suggested that this could only mean that the utricular macula, unlike the semicircular canals, furnishes two opposed modes of action.…”
Section: Functional Aspect Of the Polarization Of The Utricular Maculamentioning
confidence: 99%